Social prescribing for socially isolated older adults in rural Japan: a qualitative case study - Ota, Naho; Ebihara, Mayu; Aoki, Mizuki; Iwasawa, Atsushi; Yamazaki, Teiichiro; Jung, Songee; Makabe, Sachiko; Lynch, Mary; Rothwell, Charlotte; Illing, Jan; Nomura, Kyoko (Frontiers in Public Health, 2025)
IntroductionSocial prescribing (SP) has not yet been officially introduced in Japan. This qualitative case study aimed to identify the challenges and facilitating factors in the implementation of SP among the socially isolated older population in Akita Prefecture, Japan, based on the perspectives of general practitioners (GP), link workers (LW), and patients.MethodWe conducted a qualitative case study using semi-structured interviews and Braun & Clarke-informed thematic analysis in seven medical districts in Akita, Japan, with GP (n = 7), LW (n = 10), and older patients (n = 4).ResultsParticipants (GP and LW) emphasized that SP needed to be tailored to individual needs and that LW played a vital role as social resources in sparsely populated rural communities. The project was publicly funded; participants emphasized that, in the absence of financial support, intrinsic motivation would be important to sustaining implementation. Both groups raised concerns about ensuring LW’s competencies, the accessibility and cost of community resources, and the limited availability of such resources in rural areas. Patients highlighted that the effectiveness of SP varied by personal characteristics, and that transport barriers significantly restricted participation, highlighting the need for local support to mitigate this challenge. Establishing patients’ trust in LW and GP, along with effective communication, was viewed as essential for identifying and addressing patient-level barriers.ConclusionIn rural, resource-constrained settings such as Akita, successful SP depends on tailoring to individual needs, ensuring LW competence, and addressing transport barriers. These findings suggest that future policies should focus on sustainable funding for LW, integration with existing health and welfare systems, and mobility solutions.